2015
DOI: 10.1186/s12889-015-2142-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the influence of context in a community-based facilitation intervention focusing on neonatal health and survival in Vietnam: a qualitative study

Abstract: BackgroundIn the Neonatal health – Knowledge into Practice (NeoKIP) trial in Vietnam, local stakeholder groups, supported by trained laywomen acting as facilitators, promoted knowledge translation (KT) resulting in decreased neonatal mortality. In general, as well as in the community-based NeoKIP trial, there is a need to further understand how context influences KT interventions in low- and middle-income countries (LMICs). Thus, the objective of this study was to explore the influence of context on the facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 47 publications
(48 reference statements)
1
24
0
Order By: Relevance
“…Rather, we found that engaging leaders and other key stakeholders is vital to sustain change; although the NeoKIP trial was established in collaboration with representatives from various levels of the health system, those representatives were not sufficiently involved throughout the project’s lifetime. Again, this emphasizes the importance of assessing the needs before initiating a project, that is, by connecting to potential stakeholders and trying to understand which contextual factors might influence implementation already from the beginning [ 23 , 36 ]. Also, to tailor an intervention to include more health system representatives, particularly those in principal positions, is beneficial for achieving success and sustainability [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, we found that engaging leaders and other key stakeholders is vital to sustain change; although the NeoKIP trial was established in collaboration with representatives from various levels of the health system, those representatives were not sufficiently involved throughout the project’s lifetime. Again, this emphasizes the importance of assessing the needs before initiating a project, that is, by connecting to potential stakeholders and trying to understand which contextual factors might influence implementation already from the beginning [ 23 , 36 ]. Also, to tailor an intervention to include more health system representatives, particularly those in principal positions, is beneficial for achieving success and sustainability [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The facilitation strategy led to a reduction of neonatal mortality by almost 50% [ 22 ]. The reduction was detected during the third intervention year, indicating that facilitation is a time-consuming process, requiring substantial commitment and recognition of contextual factors [ 14 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative efforts to understand the healthcare context have previously yielded a more diverse description of context [18,19,32]. One strategy might thus be to use mixed-methods (quantitative and qualitative combined) when aiming to understand context in LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the Context Assessment for Community Health (COACH) tool was developed in Bangladesh, Vietnam, Uganda, South Africa and Nicaragua to assess modifiable aspects of the healthcare context that may influence the implementation of interventions and the integration of EBPs into clinical routines in LMICs [1416]. The COACH concept originated from the context element of the PARIHS framework [10,1719] and the interconnected health system building blocks presented by the World Health Organization (WHO) [20]. The tool evaluates health providers’ perceptions of the building blocks of the local health system.…”
Section: Introductionmentioning
confidence: 99%
“…The professionals who work with families living with the most disadvantage have a difficult task when implementing an EBP due to the demands of integrating often complex programs with their full workload and sometimes inadequate health systems (Haines, Kuruvilla, & Borchert, 2004). When implementing a program with disadvantaged communities, the practical aspects of program delivery must be taken into consideration, including the needs and capacity of the community and provider, intergenerational trauma in the community, level of complexity for the provider when moving from training to delivery in their workplace, the barriers to provider and community engagement, the availability and nature of the workforce, and the importance of community partnerships (Duong et al, 2015;Zhou et al, 2015).…”
Section: Sustained Implementation Of Evidence-based Programs In Disadmentioning
confidence: 99%